Optimal Supplemental Chromium Concentration for Alleviating Heat Stress in Broiler Chickens: A Meta-analysis - H. Kim; K. W. Lee; B. G. Kim (Tropical Animal Science Journal, 2023)
The objective of the present work was to determine the optimal supplemental chromium (Cr) concentration for alleviating the detrimental effects of heat stress on the growth performance of broilers using the literature data. A total of 53 observations from 22 experiments that assessed the growth performance of broilers fed various doses of Cr under heat stress were collected. The control groups received no supplemental Cr, whereas supplemental Cr concentrations ranged from 200 µg/kg to 2,000 µg/kg of diet. The sources of Cr were Cr chloride (n= 12), Cr-amino acid chelate (n= 14), and Cr picolinate (n= 27). The relative change (Δ %) of average daily gain (ADG) between broilers fed a Cr-supplemented diet and those fed a control diet was calculated. To compare ΔADG among Cr sources, the source was considered a fixed variable, while the experiment and the supplemental Cr concentration were considered random variables. The ΔADG was not different among the sources. Polynomial contrast analysis indicated that ΔADG increased quadratically (p<0.05) as the dietary Cr concentration increased. The optimum supplemental Cr concentration was estimated using a one-slope broken-line model with the fixed variable of supplemental Cr and a random variable of experiment based on the NLMIXED procedure of SAS. The optimum supplemental Cr concentration to maximize ΔADG in broilers under heat stress was 687 µg/kg (SE= 137, R2= 0.70, and p<0.001). Taken together, the optimum Cr supplemental concentration in broiler diets to alleviate the detrimental effects of heat stress on body weight gain is 687 µg/kg, regardless of the source of Cr.